Building the Framework for Sustainable Tourism in Príncipe Island - Francisco Silva; Miguel Roque (Tourism and Hospitality, 2024)
Like many other Small Island Developing States, São Tomé and Príncipe’s economy faces major weaknesses and constraints. These challenges are especially marked on the island of Príncipe, owing to its small size and double insularity. In recent decades, tourism, driven by international investment, has become a strategic sector for territorial development. This study assesses the suitability of this exogenous model and explores the feasibility of adopting a progressive change to a more community-centered tourism development model. Extensive fieldwork and multi-stakeholder collaboration have highlighted the need for a holistic, multi-dimensional strategy to secure this change. Such a strategy would prioritize local skills enhancement, infrastructure improvement, better governance and the diversification of tourism products and experiences. The gradual shift to a more endogenous approach in tourism development aims to strengthen sustainability across its multiple dimensions, ensuring more substantial and direct benefits for the local community and adding value to tourist services and experiences.